Respuestas

  • Usuario de Brainly
2012-06-02T21:35:27+02:00

2x-y=8 ------------- 2X = 8 + Y ----------------- X = (8 + Y) / 2  ----- Ec. (1)

3x+2y=5 ------------------------------------------------------------------ Ec. (2)

 

3x+2y=5

3 (8 + Y) / 2 + 2Y = 5

 

24 + 3Y         2Y

--------- + ------------ = 5

     2

 

24 + 3Y + 4Y

-------------------- = 5

          2

 

24 + 7Y

------------- = 5

     2

 

24 + 7Y = 5 (2)

24 + 7Y = 10

7Y = 10 - 24

7Y = -14

Y = -14/7

Y = -2

 

En la Ec (1)

2x-y=8

 

2X - (-2) = 8

2X + 2 = 8

2X = 8 - 2

2X = 6

X = 6/2

X = 3